A study on treatment adherence among patients with type 2 diabetes mellitus attending diabetic clinic - Imran, Mohammed; Plathottam, Joslin Jose (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes is one among chronic diseases requiring long term medication and its prevalence is increasing globally. Adherence to prescribed treatment among diabetes patients is very important for good glycemic control. Poor glycemic control following poor adherence is associated with increasing risk of complications, disease progression, morbidity and mortality with increasing costs of care. Hence, the present study was undertaken to assess the adherence of diabetic patients with their prescribed medications. Methods: The study involved 200 diabetic patients on oral anti-diabetic medication visiting out-patient diabetic clinic in a teaching hospital, Bangalore, who met required criteria. Information was collected using predesigned questionnaires by personally interviewing selected patients. Results: A total of 122 patients (61 %) were non-adherent with medication; 36 (18%) and 42 (21%) of patients were moderately adherent and adherent to treatment respectively. Among non adherent patients, males were more (72%) compared to females (50%), which was statistically significant (P<0.05). Non adherence was more among employed (69%) patients compared to unemployed patients (54%), this was significant statistically (p >0.05). Non adherence level was very high among males with history of smoking (80%). Conclusions: It was observed that the proportion of diabetic patients who are non-adherent to their prescribed medications was high. It is recommended that patients should be counselled repeatedly by health care providers on the importance of complying with prescribed drug regimen for better compliance and treatment outcome.